ANALISIS POTENSI TEGAKAN HUTAN RAKYAT JENIS CEMPAKA DI DESA KAWATAK KECAMATAN LANGOWAN SELATAN - Nurbaya Waisaley; Alfonsius Thomas; Wawan Nurmawan (Universitas Sam Ratulangi, 2018)
ABSTRACT Cempaka a large evergreen tree species, is one of well-know timber grow in the community forest of North Sulawesi, including in Kawatak Village, South Langowan District, Minahasa Regency. Cempaka Wasian in Sulawesi Could be divided into two species of Magnolia genus, which are Magnolia Sulawesiana and Magnolia Tsiampacca. This research aims to discover the forest stand’s potential of cempaka in Kawatak Village, South Langowan District, Minahasa Regency. The data were collected by generating sample plots with a target of 20 sample plots taken from 12 plantations with the size of 20 x 20 m plot area. In general, the existing community Forest in Kawatak Village is mixed planting pattern model spreading farmers’ land. The average volume of people‘s plantations are 185.63³ with the average volume of plantations stand of 1.177,54 m³. Keywords : Community Forest, Cempaka Potential, Kawatak Village.